Perancangan Sistem Keamanan Komputer Sekolah Menggunakan Framework Model View Controller (MVC) - Eko Fransisko Bakkara; Nanang Nanang; Syaeful Syaeful; Farida Nurlaila (Journal of Informatics, Electrical and Electronics Engineering, 2026)
The main problem faced by schools is the low level of security of academic data, such as student, teacher, grade, and administrative data, which is still managed manually or using a simple system without adequate access control mechanisms. This condition has the potential to cause data processing errors, misuse of access, and information leaks. This study aims to design and build a school computer security system that is structured, integrated, and easy to develop by implementing the Model View Controller (MVC) architecture. The research methods used include the stages of system requirements analysis, system design using Unified Modeling Language (UML), database design, system implementation based on the MVC architecture, and functional testing using the Black Box Testing method. The implementation of MVC is carried out by separating system components into Model (data management and business logic), View (user interface), and Controller (process flow controller and authentication), thereby increasing modularity, security, and ease of system maintenance. The results of the study show that the system built is able to improve data security through user authentication mechanisms, role-based authorization (role-based access control), activity monitoring, and integrated usage log recording. The separation of MVC-based architecture has been proven to minimize the risk of access errors and strengthen control over academic data management. The contribution of this research lies in: (1) designing a school computer security system model based on a structured and scalable MVC architecture, (2) implementing a role-based access control mechanism in a school environment, and (3) developing a user activity monitoring model that can be used as a reference for developing security systems in secondary educational institutions. Thus, the designed system is expected to improve the reliability of data management and support school administration processes safely, effectively, and efficiently.